Analisis Faktor-Faktor Yang Mempengaruhi Nilai Obligasi Korporasi Pada Sub Sektor Perbankan Yang Terdaftar di Bursa Efek Indonesia - Puspita Anggraini; Debi Carolina (P3M STIE Mulia Darma Pratama, 2020)
This study examines the analysis of factors affecting the value of bonds in the registered banking sub-sector in IDX. In this study the data used is secondary data that is data directly obtained from the Indonesia stock Exchange. Bond prices are usually influenced by many factors such as coupons, bond rating, Bond liquidity, due period and external factors such as JCI, interest rates, exchange rate and inflation. Independent variables in this study used coupons, interest rates, liquidity and leverage, while for the dependent variable used was the value (price) of the bonds. The number of population in this research is 43 companies engaged in banking, where the number of sample there are 38 bonds of 7 companies of banking sub-sector period of 2013-2017. In this study samples were taken in purposive sampling, namely the selection of samples based on the criteria that had been determined by the study. The analysis in this study used multiple linear regression analyses. Regression analysis serves to test the influence of independent variables (coupons, interest rates, liquidity, and leverage) on dependent variables (bond values). The results of the partial test of the study showed that coupons affect significantly and positively against the value of bonds, interest rates did not affect the value of bonds, liquidity has no effect on bond prices, and independent variables Leverage affects significantly and negatively against the value (price) of bonds. Simultaneously coupons, interest rates, liquidity and leverage affect the value (price) of bonds.